The Western Space Policies under the Influence of International Factors: Mutuality of Russia’s Case - Balcers, Valdis (Socialiniai tyrimai, 2015)
The research is dedicated to the problem of mutual dependence in space policies between the West, represented by great spacefaring actors the US and the EU, and Russia. In the study the correlation analysis, content analysis, and scenario-building methods were used. The conclusion of the analysis comprises consideration on the need to invest in their independence by Western countries in order to avoid unnecessary extra dependence on uncertain and unreliable regimes that supply substantial components for their space technology.
Keywords: correlation; interdependence; Russia; space policy